Status audiológico e marcadores de estresse oxidativo de adolescentes expostos a ruídos lazer - Correa, Bruna Machado (2016)
The aim of the study was to determine the audiological status of adolescents exposed to recreational noise and investigate the possible association between these results and oxidative stress markers. 44 individuals were evaluated, aged between 12 and 19 with normal hearing in the cross-sectional study, and 27 subjects remained in the longitudinal study. All individuals completed questionnaires regarding young people's attitudes to noise, auditory behavior and complaint of tinnitus, and hearing screening conducted by audiometry, tympanometry, recording and analysis of transient evoked otoacoustic emissions and suppression effect. Urine analysis were performed for markers of oxidative stress, from production tests of reactive oxygen species (ROS) from the ROS-DCFH-DA test and DNA damage from the PicoGreen DNA test. It was found that the adolescents had an inadequate noise exposure profile related to exposure habits at high sound pressure levels, and remained with this profile over time. There was considerable prevalence of bilateral tinnitus (31,82%), and the adolescents with the present complaint presented an ease to ignore external noises than those who did not have tinnitus. The presence of tinnitus was directly related to history of earaches (p=0,001), to the increased time of daily noise exposure reported by the teenagers (p=0,049) and the functionality of the olivocochlear system (p=0,050; 0,001). A considerable part of the sample presented absence of the suppression effect in both ears, showing change in the functioning of the olivocochlear system early. Adolescents who showed high concentrations of ROS had a higher chance of presenting higher frequency of risk factors for hearing, and showed higher levels of ROS over time. In the DNA Picogreen test, teens showed a significant increase related to DNA damage over time. The results showed an obvious public health problem that must be addressed by prevention and guidance programs to reduce or minimize risks to hearing health at this stage of life.